ETNOMATEMATIKA: IDENTIFIKASI UNSUR GEOMETRI PADA PERISAI SUKU DAYAK DI KALIMANTAN BARAT - Alvionita, Veni; Rustanuarsi, Ressy (Al-'Adad: Jurnal Tadris Matematika, 2025)
This study aims to identify mathematical elements, particularly geometric concepts, found in the shields of the Dayak tribe from West Kalimantan. This research employs a qualitative method with a descriptive exploratory approach. Data were collected through literature review and document analysis. Data analysis followed the interactive model of Miles and Huberman, which consists of four stages: data collection, data condensation, data display, and conclusion drawing. The findings reveal that the Dayak shields from West Kalimantan contain various geometric elements, including rectangles, isosceles triangles, reflectional symmetry, circles, reflection transformations, and translation transformations. This finding indicates that the Dayak shield from West Kalimantan not only holds significant historical and cultural value but also has the potential to be utilized as a resource for learning geometry.